Rome models: between history and representations (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2018)
Considered a millenarian art, the construction of models has gained in the last decades a special impulse using electronic supports in the area of archeology as well of architecture and engineering. In this text, will be presented and discussed the original and current role of the models in the historical-architectural reconstruction of the city of Rome, especially those created in the first decades of the 20th century by Giuseppe Marcelliani, Paul Bigot and Italo Gismondi.